2011
DOI: 10.1590/s1517-83822011000100008
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality and host preference of arbuscular mycorrhizal fungi of five plant species in the inner Mongolia steppe, China

Abstract: The seasonal change and host preference of arbuscular mycorrhizal (AM) colonization and community composition of five common plant species Agropyron cristatum, Anemarrhena asphodeloides, Cleistogenes squarrosa, Leymus chinensis, and Stipa grandis in the Inner Mongolia steppe were investigated. The AM root length colonization rates were different among the five plant species and were generally high in early (May and June) and late (September) growth seasons and low in August. A total of 18 AM fungal species rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 44 publications
4
13
0
1
Order By: Relevance
“…Overall, species richness and diversity indexes were higher for C. indica than for C. flaccida and W. borbonica, the latter having a low prevalence in CW over time, which was reflected in the composition and low diversity of AMF's communities in these plants. Indeed, according to Su et al [39], the season and host plant are main factors influencing spore density, species richness, and diversity of AMF, since plants can regulate carbon allocation to roots, produce secondary metabolites, and change soil environmental conditions during different growth seasons. The morphology of the root system may also justify differences in AMF communities among plants [40].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, species richness and diversity indexes were higher for C. indica than for C. flaccida and W. borbonica, the latter having a low prevalence in CW over time, which was reflected in the composition and low diversity of AMF's communities in these plants. Indeed, according to Su et al [39], the season and host plant are main factors influencing spore density, species richness, and diversity of AMF, since plants can regulate carbon allocation to roots, produce secondary metabolites, and change soil environmental conditions during different growth seasons. The morphology of the root system may also justify differences in AMF communities among plants [40].…”
Section: Resultsmentioning
confidence: 99%
“…Multivariate analysis revealed that seasons and host coaffected AM fungal spore density and species richness, and [9]. Beside seasons other factors such as disturbance [43], sporulation efficiency [44], and dormancy [45] are known to affect the abundance of AM fungal species.…”
Section: Discussionmentioning
confidence: 99%
“…To understand the ecology and function of plant-fungus associations in natural ecosystems, it is necessary to clarify seasonal diversity of AM fungi, providing insight into the factors and processes regulating ecosystem development [9]. Studies on the occurrence and diversity of AM fungi from different mangrove plants have been documented [2,10].…”
Section: Introductionmentioning
confidence: 99%
“…AM activity in steppe plant species varies with metabolic rate and nutrient demand, peaking during the active growth phase, early in the growing season, and again during the seed production stage (Su et al, 2011). If AM activity in irrigated apple orchards is also linked with metabolic rate and nutrient demand, then the higher apple root colonization rates observed in summer, compared with spring (Table 3), was probably ascribable to the high mid to late summer energy demand associated with the maturation of the apple crop.…”
Section: Effects Of Year Season and Treatment On Am Parametersmentioning
confidence: 99%